Perspektif Santri terhadap Fenomena #KaburAjaDulu dalam Budaya Kerja di Era Digital - Setiawan, Noval; Rofiki, Muhammad (Hadara : Journal of Da'wah and Islamic Civilization, 2025)
The #KaburAjaDulu phenomenon as a form of sudden resignation from the workplace has become a reflection of the resistance of the younger generation to modern work culture. Santri, as a social group with an Islamic boarding school educational background, bring distinctive religious and moral values ​​in facing the reality of a competitive work world that often conflicts with their idealistic principles. This study aims to analyze the perspective of santri on the #KaburAjaDulu phenomenon and examine the factors behind the decision. Using a qualitative approach with the theory of person-organization fit and cultural resistance, data were collected through in-depth interviews with 12 alumni of Islamic boarding schools An-Nawawi Purworejo who had experienced sudden resignation. The results of the study showed that the inconsistency between religious values ​​and organizational culture, structural injustice, and the lack of space for self-actualization were the main drivers of santri choosing #KaburAjaDulu. This study emphasizes the importance of understanding personal values ​​in managing human resources and designing a more culturally inclusive workplace.